Method for manufacturing modified wooden material used for manufacturing wooden compact with wooden texture
By modifying wood with specific organic bases and hydrocarbonated hydrocarbons at room temperature, the method addresses inefficiencies and appearance issues in existing wood processing, enabling efficient production of wood-textured products with improved resin compatibility and color retention.
Patent Information
- Application Number
- JP2024202171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Existing methods for manufacturing wood products with a wood texture require high temperatures, which are inefficient and costly, and result in undesirable changes to the wood's appearance and properties.
A method involving the use of specific organic bases to modify wood, followed by contact with hydrocarbonated hydrocarbons at room temperature to introduce functional groups, such as hydrocarbon groups, onto the wood surface, thereby creating a modified wood suitable for wood-textured products.
The method allows for efficient production of modified wood with desired functional groups at room temperature, reducing thermal damage and maintaining the wood's appearance, making it easier to design products with the original wood's hue and improving its compatibility with resins.
Smart Images

Figure 2025015786000005 
Figure 2025015786000006 
Figure 2025015786000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing modified wood suitable as a raw material for producing processed products (wooden molded products) having the texture of wood. [Background technology]
[0002] In recent years, technology has been developed to manufacture building materials, furniture, tableware, gardening supplies, stationery, toys, musical instruments, etc., with the texture of wood by using small pieces or powder of wood together with resin. In this case, it is considered preferable that the wood be pretreated to have a chemically modified surface, and surface treatments have been studied to activate the hydroxyl groups contained in the wood and make it more susceptible to reaction with various reagents.
[0003] For example, Non-Patent Document 1 describes a technology in which a predetermined amount of 40% caustic soda solution is added to poplar wood flour, allowed to penetrate the wood flour for 3 to 4 minutes, the liquid is removed by squeezing, a predetermined amount of benzyl chloride is then added, and etherification treatment is carried out at 110°C. After the reaction, the treated wood flour is put into methanol, filtered, washed with methanol, and then vacuum dried to produce modified wood flour. Non-Patent Document 2 describes a technology for producing a sample with a plasticized surface by immersing air-dried wood (beech, etc.) in an approximately 40% aqueous solution of sodium hydroxide at room temperature, reacting it in a benzyl chloride solution at 110°C, and then washing the treated sample with water, drying it, and thermo-compressing it. Furthermore, Non-Patent Document 3 describes that wood flour is pretreated with a high-concentration aqueous solution of sodium hydroxide, and then benzyl chloride is added thereto, followed by heating and stirring to effect benzylation.
[0004] Furthermore, Patent Document 1 discloses a method for treating wood, which is characterized by impregnating wood or wood-based materials with a quaternary ammonium salt in an alkaline atmosphere of pH 7 or higher and causing a chemical reaction during or after the impregnation. Specifically, it describes how two-sided straight-grained beech specimens were immersed in a thermostatically controlled pressurized tank containing an aqueous solution of lauryl benzyl trimethyl ammonium chloride (pH 8) maintained at 85°C, and treated for two hours under conditions of 85°C and 11.5 atm. Patent Document 2 discloses a method for producing a cellulose ether derivative, which comprises producing alkali cellulose by mechanically treating cellulose in the presence of water and alkali in a specific ratio, and reacting the obtained alkali cellulose with an alkyl halide, an alkylene oxide, a halogenated acetic acid, or a vinyl monomer as an etherification agent. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2-47001 [Patent Document 2] JP 2011-37924 A [Non-patent literature]
[0006] [Non-Patent Document 1] Norimoto Kyo et al., Wood Research and Materials, 17:181-191 (1983) [Non-Patent Document 2] Tsutomu Aoki et al., Wood Research and Materials, 22:66-77 (1986) [Non-Patent Document 3] Journal of Polymer Science: Part A: Polymer chemistry, 27, 2457-2482 (1989) Summary of the Invention [Problem to be solved by the invention]
[0007] In the methods described in Non-Patent Documents 1, 2, and 3, when the raw wood material is contacted with sodium hydroxide and then with benzyl chloride (modifying compound), a high temperature of, for example, 110°C is required, which is not economical. The object of the present invention is to provide a method for efficiently producing modified wood suitable as a raw material for producing processed products (wood-based molded products) having the texture of wood. [Means for solving the problem]
[0008] The present inventors have found that a first step of contacting raw wood with a specific organic base produces modified wood (hereinafter referred to as "first modified wood") that is easy to react with a modifying compound. They have also found that a modified wood (hereinafter referred to as "second modified wood") suitable as a raw material for manufacturing processed products having the texture of wood can be efficiently obtained by further contacting the first modified wood with a modifying compound such as a halogenated hydrocarbon.
[0009] The present invention is illustrated below. [1] A method for producing modified wood, comprising a first step of contacting raw wood with a compound (A) represented by the following general formula (1): [R + ][OH - ] (1) (In the formula, R + is an organic cation. [2] The above organic cation R + The method for producing modified wood material according to the above [1], wherein is a quaternary phosphonium cation. [3] The method for producing modified wood material according to [1] or [2] above, wherein in the first step, the raw wood material is brought into contact with an aqueous solution of the compound (A). [4] A method for producing modified wood material according to any one of [1] to [3] above, further comprising a second step of contacting the modified wood material obtained in the first step with a modifying compound. [5] The method for producing modified wood material according to the above [4], wherein the modifying compound used in the second step is a halogenated hydrocarbon, and forms a hydrocarbon group on the surface of the modified wood material. [6] The method for producing modified wood material according to the above [5], wherein the halogenated hydrocarbon is a chlorine compound or a bromine compound. Effect of the Invention
[0010] In the manufacturing method of the present invention, the modified wood obtained through the first and second steps is suitable as a raw material for manufacturing processed products having the texture of wood. The raw wood used in the first step is rich in hydroxyl groups of cellulose chains, but the first step can make the modified wood in a chemical state that is easy to chemically modify, and in the second step, a modifying compound (halogenated hydrocarbon, α-halogen acid, alkylene chlorohydrin, dialkyl sulfuric acid, acrylonitrile, alkylene oxide, diazo compound, β-lactone, fatty acid, fatty acid anhydride, fatty acid halide, alkylketene, dialkyl carbonate, alkoxysilane, alkoxysiloxane, silazane, silyl halide, silyl trifluoromethanesulfonate, etc.) can be efficiently reacted without requiring high temperature conditions. As a result, modified wood having the desired functional groups on the surface can be obtained. In addition, since the second step can be performed at room temperature of 20°C to 30°C, damage due to heat can also be suppressed. When the modifying compound is, for example, a halogenated hydrocarbon, a hydrocarbon group (more precisely, an OR group (wherein R is a hydrocarbon group) such as an alkoxy group, an aryloxy group, or an aralkyloxy group) can be formed on the surface of the modified wood, and when the modifying compound is a carboxylic acid or a carboxylic anhydride, a carboxylic acid ester group can be formed on the surface of the modified wood. In addition, the modified wood obtained tends to have a smaller difference in appearance, such as hue, compared to the raw wood, making it easier to design products that use modified wood based on the hue of the raw wood. [Brief description of the drawings]
[0011] [Figure 1] 1 shows infrared absorption spectra of each of the modified wood materials obtained in Example 1-1 and Comparative Example 1-3 and the untreated raw wood material (defatted wood flour). [Diagram 2]FIG. 2 is an explanatory diagram of a method for determining the intensity of an absorption peak due to OH stretching vibration detected in the range of 3000 to 3600 cm −1 and the intensity of an absorption peak due to CH stretching vibration detected in the range of 2800 to 3000 cm −1 . [Diagram 3] FIG. 2 is an explanatory diagram of a method for determining the intensity of an absorption peak derived from a mono-substituted benzene ring detected at 680 to 714 cm −1 . [Figure 4] 2 shows infrared absorption spectra of each modified wood material obtained in Example 2-1 and Comparative Example 2-2 and untreated raw wood material (defatted wood chips). [Diagram 5] 1 is an optical microscope image of the surface of the untreated raw wood (defatted wood chips) used in Example 2-1. [Figure 6] 1 is an optical microscope image of the surface of modified wood (RR1) obtained in Example 2-1. [Figure 7] 1 is an optical microscope image of the surface of modified wood (SS2-2) obtained in Comparative Example 2-2. [Figure 8] 1 is an infrared absorption spectrum of the modified wood (SS2-2) obtained in Comparative Example 2-2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, "raw wood" refers to wood that has been processed into a specific shape such as a board before being subjected to the first step, or wood that has been subdivided by grinding, chopping, pulverizing, defibrating, or other methods to have the form of chips, fibers, powder, etc. The resulting "modified wood" may have the same shape or size as the "raw wood".
[0013] The first step in the present invention is a step of contacting raw wood with a compound (A) represented by the following general formula (1). [R + ][OH - ] (1) (In the formula, R + is an organic cation.
[0014] The raw material wood is not particularly limited, and examples thereof that can be used include conifers such as cedar, cypress, and pine; broad-leaved trees such as poplar, beech, oak, and birch; bamboo; hemp species such as jute, kenaf, flax, hemp, ramie, and sisal; and herbaceous plants.
[0015] The compound (A) is represented by the above general formula (1), and in the first step, only one type of compound (A) may be used, or two or more types of compound (A) may be used. In the above general formula (1), R + is an organic cation. This organic cation R + is not particularly limited, and examples thereof include those having a nitrogen atom as the ion center, those having a sulfur atom as the ion center, those having a phosphorus atom as the ion center, and further those having a nitrogen atom and a sulfur atom as the ion center, etc. In the present invention, those having a nitrogen atom as the ion center and those having a phosphorus atom as the ion center are preferred.
[0016] Examples of the cation having a nitrogen atom as the ion center include tetraalkylammonium cation, imidazolium cation, pyridinium cation, quinolinium cation, pyrrolidinium cation, piperazinium cation, piperidinium cation, morpholinium cation, pyridazinium cation, pyrimidinium cation, pyrazinium cation, pyrazolium cation, thiazolium cation, oxazolium cation, triazolium cation, guanidium cation, etc. Among these, quaternary ammonium cations such as tetraalkylammonium cation, imidazolium cation, pyridinium cation, pyrrolidinium cation, piperazinium cation, piperidinium cation, morpholinium cation, etc. are preferred.
[0017] Examples of the tetraalkylammonium cation include tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, tetrapentylammonium, tetrahexylammonium, tetraheptylammonium, tetraoctylammonium, tetranonylammonium, tetradecylammonium, tetradodecylammonium, ethyltrimethylammonium, diethyldimethylammonium, triethylmethylammonium, tetraethylammonium, trimethylpropylammonium, trimethylisopropylammonium, ethyldimethylpropylammonium, ethyldimethylisopropylammonium, diethylmethylpropylammonium, diethylmethylisopropylammonium, dimethyldipropylammonium, dimethylpropylisopropylammonium, dimethyldiisopropylammonium, triethylpropylammonium, butyltrimethylammonium, isobutyltrimethylammonium, tert-butyl ... Examples of cations include cations derived from t-butyltrimethylammonium, triethylisopropylammonium, ethylmethyldipropylammonium, ethylmethyldiisopropylammonium, butylethyldimethylammonium, isobutylethyldimethylammonium, tert-butylethyldimethylammonium, diethyldipropylammonium, diethylpropyldiisopropylammonium, diethyldiisopropylammonium, methyltripropylammonium, methyldipropylisopropylammonium, methylpropyldiisopropylammonium, butyltriethylammonium, isobutyltriethylammonium, tert-butyltriethylammonium, dibutyldimethylammonium, diisobutyldimethylammonium, ditert-butyldimethylammonium, butylisobutyldimethylammonium, butyl-tert-butyldimethylammonium, isobutyl-tert-butyldimethylammonium, trioctylmethylammonium, and the like.
[0018] Examples of the cation having a phosphorus atom as the ion center include quaternary phosphonium cations, which are phosphonium cations having four hydrocarbon groups (alkyl groups, aryl groups, or alkylaryl groups). Examples of the quaternary phosphonium cation include tetramethylphosphonium, tetraethylphosphonium, tetrapropylphosphonium, tetrabutylphosphonium, tetrapentylphosphonium, tetrahexylphosphonium, tetraheptylphosphonium, tetraoctylphosphonium, tetranonylphosphonium, tetradecylphosphonium, tetraphenylphosphonium, 1,1,1-tributyl-1-octylphosphonium, 1,1,1-tributyl-1-nonylphosphonium, 1,1,1-tributyl-1-decylphosphonium, 1,1,1- Tributyl-1-undecylphosphonium, 1,1,1-tributyl-1-dodecylphosphonium, 1,1,1-tributyl-1-tridecylphosphonium, 1,1,1-tributyl-1-tetradecylphosphonium, 1,1,1-tributyl-1-pentadecylphosphonium, 1,1,1-tributyl-1-hexadecylphosphonium, 1,1,1-tributyl-1-heptadecylphosphonium, 1,1,1-tributyl-1-octadecylphosphonium, 1,1,1-tributyl-1-nonadecylphosphonium, 1,1,1-tributyl-1- Icosylphosphonium, 1,1,1-tripentyl-1-octylphosphonium, 1,1,1-tripentyl-1-nonylphosphonium, 1,1,1-tripentyl-1-decylphosphonium, 1,1,1-tripentyl-1-undecylphosphonium, 1,1,1-tripentyl-1-dodecylphosphonium, 1,1,1-tripentyl-1-tridecylphosphonium, 1,1,1-tripentyl-1-tetradecylphosphonium, 1,1,1-tripentyl-1-pentadecylphosphonium, 1,1,1-tripentyl-1-hexadecylphosphonium phosphonium, 1,1,1-tripentyl-1-heptadecylphosphonium, 1,1,1-tripentyl-1-octadecylphosphonium, 1,1,1-tripentyl-1-nonadecylphosphonium, 1,1,1-tripentyl-1-icosylphosphonium, 1,1,1-trihexyl-1-octylphosphonium, 1,1,1-trihexyl-1-nonylphosphonium, 1,1,1-trihexyl-1-decylphosphonium, 1,1,1-trihexyl-1-undecylphosphonium, 1,1,1-trihexyl-1-dodecylphosphonium, 1,1,1-Trihexyl-1-tridecylphosphonium, 1,1,1-trihexyl-1-pentadecylphosphonium, 1,1,1-trihexyl-1-hexadecylphosphonium, 1,1,1-trihexyl-1-heptadecylphosphonium, 1,1,1-trihexyl-1-octadecylphosphonium, 1,1,1-trihexyl-1-nonadecylphosphonium, 1,1,1-trihexyl-1-icosylphosphonium, 1,1,1-triheptyl-1-octylphosphonium, 1,1,1-triheptyl-1-octylphosphonium, 1,1,1-triheptyl-1- Nonylphosphonium, 1,1,1-triheptyl-1-decylphosphonium, 1,1,1-triheptyl-1-undecylphosphonium, 1,1,1-triheptyl-1-dodecylphosphonium, 1,1,1-triheptyl-1-tridecylphosphonium, 1,1,1-triheptyl-1-tetradecylphosphonium, 1,1,1-triheptyl-1-pentadecylphosphonium, 1,1,1-triheptyl-1-hexadecylphosphonium, 1,1,1-triheptyl-1-heptadecylphosphonium, 1, 1,1-triheptyl-1-octadecylphosphonium, 1,1,1-triheptyl-1-nonadecylphosphonium, 1,1,1-triheptyl-1-icosylphosphonium, 1,1,1,1-tetraoctylphosphonium, 1,1,1-trioctyl-1-nonylphosphonium, 1,1,1-trioctyl-1-decylphosphonium, 1,1,1-trioctyl-1-undecylphosphonium, 1,1,1-trioctyl-1-dodecylphosphonium, 1,1,1-trioctyl-1-tridecylphosphonium Examples of cations include cations derived from tetraalkylphosphonium cations such as 1,1,1-trioctyl-1-tetradecylphosphonium, 1,1,1-trioctyl-1-pentadecylphosphonium, 1,1,1-trioctyl-1-hexadecylphosphonium, 1,1,1-trioctyl-1-heptadecylphosphonium, 1,1,1-trioctyl-1-octadecylphosphonium, 1,1,1-trioctyl-1-nonadecylphosphonium, and 1,1,1-trioctyl-1-icosylphosphonium. In addition, cations derived from benzyltrimethylphosphonium, tetraphenylphosphonium, tetranaphthylphosphonium, trimethylphenylphosphonium, etc. can also be used.
[0019] In the first step according to the present invention, the method for contacting the raw wood with the compound (A) is not particularly limited.
[0020] When compound (A) is a solid, the raw wood material can be brought into contact with a solution obtained by dissolving compound (A) in a medium that does not cause deterioration or decomposition of the raw wood material.
[0021] Furthermore, when compound (A) is a liquid, it may be brought into contact with the raw wood as is, or the raw wood may be brought into contact with a solution obtained by dissolving compound (A) in a medium that does not cause deterioration or decomposition of the raw wood. Examples of the medium include water; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, and ethylene glycol; ethers such as diethyl ether and diisopropyl ether; carboxylic acids such as acetic acid and propionic acid; carboxylic acid esters such as ethyl acetate and methyl propionate; carboxylic acid anhydrides such as acetic anhydride; tetrahydrofuran, 1,4-dioxane, acetone, ethyl methyl ketone, carbon tetrachloride, chloroform, dichloromethane, dichloroethane, benzene, toluene, and xylene; alkanes such as cyclohexane, pentane, hexane, and heptane; acetonitrile, nitromethane, dimethylformamide, and hexamethylphosphoric triamide; amines such as triethylamine; pyridine, imidazole, dimethyl sulfoxide, dimethylacetamide, and carbon disulfide; and ionic liquids such as 1-butyl-3-methylimidazolium chloride, with water being preferred.
[0022] In the present invention, regardless of the properties of compound (A), it is preferable to contact a solution of compound (A) with the raw wood, and it is particularly preferable to contact an aqueous solution of compound (A) with the raw wood. When a solution of compound (A) is used, the concentration of compound (A) is preferably 40 to 70% by mass.
[0023] When using a liquid compound (A) or a solution of compound (A), the raw wood and compound (A) can be contacted by the following method. (A) A method of immersing raw wood in a liquid containing compound (A) (a) A method of stirring raw wood in a liquid containing compound (A) (c) A method of spraying a liquid containing compound (A) onto raw wood.
[0024] The temperature at which the raw wood material and the compound (A) are contacted is not particularly limited as long as it does not cause deterioration or decomposition of the raw wood material, but is usually 200°C or lower, preferably -20°C to 100°C, and more preferably 0°C to 50°C. The contact time between the raw wood material and the compound (A) is appropriately selected depending on the shape, size, etc. of the raw wood material, but is usually 5 minutes or more.
[0025] After contacting the raw wood with the compound (A), the compound (A) attached to the raw wood is removed to obtain modified wood (first modified wood) that is easy to react with the modifying compound. The method for removing the compound (A) is not particularly limited, but for example, a method of washing the modified wood with a medium that can dissolve the compound (A) without causing deterioration or decomposition of the modified wood, and then drying the modified wood, etc. can be applied. Drying after washing can be performed by heated air drying, reduced pressure drying, etc.
[0026] Although the inventors have not specified the structure of the first modified wood obtained in the first step, they believe that the first modified wood is in a chemical state in which the charges are slightly unevenly distributed between the hydrogen atoms and oxygen atoms in the hydroxyl groups of the raw wood, which is rich in hydroxyl groups derived from cellulose chains, so that the hydrogen atoms in the hydroxyl groups of the raw wood have a positive charge and the oxygen atoms have a negative charge, or a state close to that. Furthermore, since the first modified wood is not sufficient as a raw material for manufacturing processed products having the texture of wood, it is possible to obtain modified wood (second modified wood) suitable as a raw material for manufacturing processed products having the texture of wood by further modifying the surface of this first modified wood.
[0027] The second step according to the present invention is a step of contacting the first modified wood with a modifying compound, such as halogenated hydrocarbons, α-halogen acids, alkylene chlorohydrins, dialkyl sulfuric acids, acrylonitrile, alkylene oxides, diazo compounds, β-lactones, fatty acids, fatty acid anhydrides, fatty acid halides, alkylketenes, dialkyl carbonates, alkoxysilanes, alkoxysiloxanes, silazanes, silyl halides, and silyl trifluoromethanesulfonates.
[0028] By using halogenated hydrocarbons, α-halogen acids, alkylene chlorohydrins, dialkyl sulfuric acids, acrylonitrile, alkylene oxides, diazo compounds, or β-lactones as modifying compounds, most of the OH groups of the hydroxyl groups derived from the cellulose chains are converted to OR. 1 (R 1 Therefore, the surface of the second modified wood obtained has a hydrocarbon group R 1 In this case, it is preferable to use halogenated hydrocarbons, more preferably chlorine and bromine compounds, and especially bromine compounds. In addition, by using fatty acids, fatty acid anhydrides, or fatty acid halides as modifying compounds, the OH of the hydroxyl groups derived from the cellulose chain can be converted to OC(O)OR. 2 (R 2 : Hydrocarbon groups).
[0029] In the second step according to the present invention, the method for contacting the first modified wood with the modifying compound is not particularly limited.
[0030] When the modifying compound is a solid, the modifying compound can be dissolved in a medium that does not cause deterioration or decomposition of the first modified wood, and the first modified wood can be brought into contact with the obtained solution.
[0031] Furthermore, if the modifying compound is liquid, it may be brought into contact with the first modified wood as is, or the modifying compound may be dissolved in a medium that does not cause deterioration or decomposition of the first modified wood, and the resulting solution may be brought into contact with the first modified wood. Examples of the medium include water; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, and ethylene glycol; ethers such as diethyl ether and diisopropyl ether; carboxylic acids such as acetic acid and propionic acid; carboxylic acid esters such as ethyl acetate and methyl propionate; carboxylic acid anhydrides such as acetic anhydride; tetrahydrofuran, 1,4-dioxane, acetone, ethyl methyl ketone, carbon tetrachloride, chloroform, dichloromethane, dichloroethane, benzene, toluene, and xylene; alkanes such as cyclohexane, pentane, hexane, and heptane; acetonitrile, nitromethane, dimethylformamide, and hexamethylphosphoric triamide; amines such as triethylamine; pyridine, imidazole, dimethyl sulfoxide, dimethylacetamide, and carbon disulfide; and ionic liquids such as 1-butyl-3-methylimidazolium chloride. The medium can be one or more of these.
[0032] In the present invention, regardless of the nature of the modifying compound, it is preferable to bring a solution of the modifying compound into contact with the first modified wood. When a solution of the modifying compound is used, the concentration of the modifying compound is preferably 10 to 100% by mass.
[0033] When a liquid modifying compound is used, or when a solution of the modifying compound is used, the first modified wood and the modifying compound can be contacted by the following method. (A) A method of immersing the first modified wood in a liquid containing a modifying compound. (a) A method of stirring the first modified wood in a liquid containing a modifying compound. (c) A method of spraying a liquid containing a modifying compound onto the first modified wood
[0034] The temperature when the first modified wood is brought into contact with the modifying compound is not particularly limited as long as the first modified wood is not altered or decomposed, but since a desired high modification effect can be obtained, the temperature is preferably 200° C. or lower, more preferably −20° C. to 100° C., and even more preferably 0° C. to 80° C. In addition, since the appearance of the obtained second modified wood is not significantly different from that of the raw material wood, it becomes easy to design a product using the second modified wood as a raw material for manufacturing a processed product having the texture of wood, based on the hue of the raw material wood. The contact time between the first modified wood and the modifying compound is appropriately selected depending on the shape, size, etc. of the first modified wood, but is usually 5 minutes or more.
[0035] After the first modified wood and the modifying compound are brought into contact with each other, the liquid containing the modifying compound and residues that are merely attached to the first modified wood can be removed to obtain the second modified wood that is the object of the present invention. The method for removing the liquid containing the modifying compound and the like that is merely attached is not particularly limited, but for example, a method of washing the modified wood with a medium that can dissolve the modifying compound without causing deterioration or decomposition of the modified wood, and then drying the modified wood can be applied. Drying after washing can be performed by heated air drying, drying under reduced pressure, etc.
[0036] When the modifying compound is a halogenated hydrocarbon, the surface is provided with a hydrocarbon group R 1The degree of modification by halogenated hydrocarbons can be confirmed by infrared absorption spectroscopy. FIG. 1 shows infrared absorption spectra obtained by FT-IR measurement of wood flour before and after modification when defatted cedar wood flour is used as raw wood, tetrabutylphosphonium hydroxide is used as compound (A), and benzyl bromide is used as a modifying compound. In the infrared absorption spectra of the defatted wood flour (raw wood) and modified wood MM1 (second modified wood), the 2800-3000 cm -1 The CH stretching vibration absorption peak at 3000-3600 cm -1 Both the absorption peaks due to OH stretching vibrations in the modified wood MM1 and the modified wood MM2 can be confirmed. When the intensity ratios of these absorption peaks (OH / CH ratio) are calculated and compared, the present invention makes it possible to reduce the amount of hydroxyl groups in the OH / CH ratio of the second modified wood to preferably 1 / 2 or less, more preferably 1 / 3 or less, relative to the OH / CH ratio of the raw wood. In the case of FIG. 1, the OH / CH ratio of the defatted wood flour (raw wood) is 3.4, and the OH / CH ratio of the modified wood MM1 (second modified wood) is 0.7. From these results, it can be seen that about 80% of the hydroxyl groups in the defatted wood flour (raw wood) are OR. 1 It can be seen that it has been modified into
[0037] In addition, the surface is a hydrocarbon group R 1 The surface of the second modified wood, which is rich in hydrophilicity, has a large contact angle with water, and can be said to be more hydrophobic than the raw wood. Therefore, when the second modified wood is used in combination with a general-purpose resin, it is easier to produce a molded product than when untreated raw wood is used.
[0038] The resin used in the manufacture of the molded body may be either a thermoplastic resin or a curable resin. Examples of the thermoplastic resin include acrylic resin, polyolefins such as polyethylene and polypropylene, cyclic polyolefins, polyethylene glycol, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, polytetrafluoroethylene, ABS resin, AS resin, polyamides such as nylon, polyacetal, polycarbonate, modified polyphenylene ether, polyester resins such as polybutylene terephthalate and polyethylene terephthalate, polyphenylene sulfide, polysulfone, polyethersulfone, amorphous polyarylate, liquid crystal polymers, polyetheretherketone, polyimide, polyamideimide, and the like. Examples of the curable resin include phenolic resin, epoxy resin, unsaturated polyester, urea resin, melamine resin, diallyl phthalate, silicon resin, vinyl ester resin, polyimide, polyurethane, and the like. When a curable resin is used, a curing agent can be used in combination. The above resin may further contain a plasticizer, an antioxidant, an ultraviolet absorber, an antiaging agent, a filler, an antibacterial agent, an antiseptic, an antistatic agent, and the like. EXAMPLES
[0039] In order to more specifically describe the configuration and effects of the present invention, examples are given below, but the present invention is not limited to these examples. In the following examples and comparative examples, "parts" and "%" are all based on mass.
[0040] 1. Manufacturing and evaluation of modified wood (1) In this example, the raw wood material used was defatted wood flour obtained by degreasing cedar wood flour (particle size: 150 to 300 μm) with hot water and methanol, and then drying under reduced pressure at 25° C. for 24 hours or more.
[0041] Example 1-1 0.5 g of defatted wood flour was placed in a flask with a capacity of 50 mL, and then tetrabutylphosphonium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (hereinafter referred to as “[P 44444 mL of a 50% by weight aqueous solution of [P OH" was added dropwise and spread over the entire wood powder. The mixture was then stirred at 25°C using a 1 cm long rugby ball-shaped fluororesin stirrer to obtain the first modified wood (M1). 4444 ]OH treatment time is [P 4444 The time elapsed after the OH aqueous solution was dropped onto the defatted wood flour was 5 minutes in total. Then, 4 mL of benzyl bromide was added and stirred at 25°C for 1 hour, followed by Soxhlet extraction with methanol for 18 hours, and then washing with Soxhlet extraction with water for 18 hours. The wood was then dried under reduced pressure at 25°C for 24 hours or more to obtain the second modified wood (MM1).
[0042] The obtained second modified wood (MM1) and the defatted wood flour before treatment were measured by total reflection measurement using a Thermo Fisher infrared spectrophotometer "NICOLET 6700 FT-IR" (model name) in the measurement wave number range of 4000 to 500 cm -1 The infrared absorption spectrum was obtained by measuring the absorption peak due to the OH stretching vibration of the defatted wood flour before the treatment (3000-3600 cm) in the second modified wood (MM1). -1 ) is significantly reduced, and the absorption peak due to the benzyl moiety in the benzyloxy group is at 3020-3080 cm -1 , 1592~1612cm -1 , 1454~1496cm -1 , about 736cm -1 and approximately 696 cm -1 This indicates that the hydroxyl groups in the defatted wood flour were modified to benzyloxy groups (see Figure 1).
[0043] Next, in order to grasp the progress of the reaction, the decrease rate of the absorption peak intensity derived from the hydroxyl group and the increase rate of the absorption peak intensity derived from the benzene ring were calculated. The decrease rate of the absorption peak intensity derived from the hydroxyl group was 2800 to 3000 cm -1 The CH stretching vibration-derived absorption peak intensity at 3000-3600 cm -1The increase rate of the absorption peak intensity due to the benzene ring was calculated from the ratio of the absorption peak intensity due to the CH stretching vibration to the absorption peak intensity due to the 680-714 cm -1 The benzylation rate was calculated from the ratio of the absorption peak intensity derived from the monosubstituted benzene ring that appears in the sample (Bn / CH ratio, see Figure 3). Measurements were performed on multiple samples, and the average values are shown in Table 1. The smaller the OH / CH ratio and the larger the Bn / CH ratio, the more benzylated the sample is.
[0044] Example 1-2 The second modified wood (MM2) was obtained by the same procedure as in Example 1-1, except that the treatment temperature when benzyl bromide was added was changed from 25° C. to 7° C. Then, FT-IR measurement was performed, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0045] Examples 1-3 The same operation as in Example 1-1 was carried out to obtain the second modified wood (MM3), except that the treatment temperature when benzyl bromide was added was changed from 25° C. to 50° C. Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0046] Examples 1-4 The second modified wood (MM4) was obtained by the same procedure as in Example 1-1, except that the treatment temperature when benzyl bromide was added was changed from 25° C. to 75° C. Then, FT-IR measurement was performed, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0047] Examples 1-5 The same operation as in Example 1-1 was carried out except that the treatment time when benzyl bromide was added was changed from 1 hour to 10 minutes, and the second modified wood (MM5) was obtained. Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0048] Comparative Example 1-1 [P 4444The same procedure as in Example 1-1 was carried out except that a 40% by mass aqueous solution of sodium hydroxide was used instead of the OH aqueous solution, to obtain a second modified wood (NN1). Then, FT-IR measurements were carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0049] Comparative Example 1-2 [P 4444 The same operation as in Example 1-1 was carried out except that a 40% by mass aqueous solution of sodium hydroxide was used instead of the OH aqueous solution, the treatment temperature when benzyl bromide was added was changed from 25°C to 110°C, and the treatment time was changed from 1 hour to 2 hours, to obtain a second modified wood (NN2). Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0050] Comparative Example 1-3 [P 4444 ] The same operation as in Example 1-1 was carried out except that 40 mass% sodium hydroxide aqueous solution was used instead of OH aqueous solution, benzyl chloride was used instead of benzyl bromide, the treatment temperature with benzyl chloride was changed from 25 ° C to 110 ° C, and the treatment time was changed from 1 hour to 2 hours, to obtain a second modified wood (NN3). Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 1).
[0051] [Table 1]
[0052] The following can be seen from Table 1. That is, the defatted wood flour had an OH / CH intensity ratio of 3.4 and a Bn / CH intensity ratio of 0.1, whereas in Examples 1-1 to 1-5 and Comparative Examples 1-2 and 1-3, the OH / CH intensity ratio was 0.4 to 0.9 and the Bn / CH intensity ratio was 4.5 to 7.3, indicating that benzylation had occurred. In particular, in Examples 1-1 and 1-5, the [P 4444It can be seen that the treatment temperature in the second step after using an aqueous solution of ]OH was set to 25°C, and the reaction proceeded efficiently. It can be seen from Example 1-5 that the reaction proceeded sufficiently even when the contact time of benzyl bromide was as short as 10 minutes. On the other hand, in Comparative Example 1-1 in which an aqueous solution of sodium hydroxide was used, it was found that almost no benzylation occurred when the treatment temperature in the second step was set to 25°C. It can be seen from Comparative Examples 1-2 and 1-3 that in order to sufficiently proceed with benzylation, it is necessary to increase the treatment temperature in the second step to 110°C.
[0053] 2. Manufacturing and evaluation of modified wood (2) In this example, the raw wood used was a cedar tangential grain test piece (tangential direction T: 20 mm, radial direction R: 5 mm, transition direction L: 20 mm) that had been degreased with hot water and methanol, dried at 105°C for 2 hours, and then returned to room temperature to obtain a defatted wood piece (approximately 0.7 g).
[0054] Example 2-1 On the bottom of the petri dish, [P 4444 0.5 mL of a 50% by mass aqueous solution of ]OH was dropped, and the grain side of the degreased wood piece was immersed in the solution and left to stand at 25°C for 10 minutes. The wood piece was then removed, and the liquid adhering to the surface was wiped off with wiping paper. Next, 0.5 mL of benzyl bromide was dropped onto the bottom of another petri dish, and the grain side of the wood piece was immersed in the solution and left to stand at 25°C for 10 minutes. Then, Soxhlet extraction was performed using methanol for 18 hours, and then Soxhlet extraction was performed using water for 18 hours to wash the wood. After that, the wood was dried by blowing air at 25°C for 18 hours and at 105°C for 4 hours to obtain the second modified wood (RR1).
[0055] The obtained second modified wood (RR1) and the untreated degreased wood pieces were both measured on the tangential surface using the above-mentioned infrared spectrophotometer in the measurement wave number range of 4000 to 500 cm -1 The infrared absorption spectrum was obtained by FT-IR measurement (ATR method). As a result, in the second modified wood (RR1), the benzylation treatment caused an absorption peak (3000-3600 cm) due to the OH stretching vibration derived from the defatted wood flour before treatment. -1) is significantly reduced, and the absorption peak due to the benzyl moiety in the benzyloxy group is at 3020-3080 cm -1 , 1592~1612cm -1 , 1454~1496cm -1 , about 736cm -1 and approximately 696 cm -1 This indicated that the hydroxyl groups in the defatted wood chips had been converted to benzyloxy groups (see Figure 4). In order to grasp the progress of the reaction, the OH / CH intensity ratio and the Bn / CH intensity ratio were calculated in the same manner as in Example 1-1. The measurements were performed on multiple samples, and the average values are shown in Table 2.
[0056] Example 2-2 The same operation as in Example 2-1 was carried out except that the treatment time when benzyl bromide was added was changed from 10 minutes to 1 hour, and the second modified wood (RR2) was obtained. Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 2).
[0057] Example 2-3 The same procedure as in Example 2-1 was carried out except that benzyl chloride was used instead of benzyl bromide, to obtain the second modified wood (RR3). Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 2).
[0058] Comparative Example 2-1 [P 4444 The same operation as in Example 1-1 was carried out except that 40% by mass sodium hydroxide solution was used instead of the OH aqueous solution, the treatment time was changed from 10 minutes to 1 hour, and then benzyl chloride was used instead of benzyl bromide, to obtain the second modified wood (SS1). Then, FT-IR measurement was carried out, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 2).
[0059] Comparative Example 2-2 [P 4444] Instead of the OH aqueous solution, a 40% by mass sodium hydroxide aqueous solution was used, the treatment time was changed from 10 minutes to 1 hour, and then, instead of benzyl bromide, benzyl chloride was used, the treatment temperature with benzyl chloride was changed from 25°C to 110°C, and the treatment time was changed from 10 minutes to 2 hours. Except for this, the same operation as in Example 2-1 was performed to obtain a second modified wood (SS2). Then, FT-IR measurement was performed, and the OH / CH ratio and Bn / CH ratio were calculated (see Table 2).
[0060] [Table 2]
[0061] The following can be seen from Table 2. That is, the OH / CH intensity ratio was 3.6 and the Bn / CH intensity ratio was 0.3 in the defatted wood chips, whereas the OH / CH intensity ratio was 0.6 to 0.7 and the Bn / CH intensity ratio was 8.8 to 9.4 in Examples 2-1 and 2-2 and Comparative Example 2-2, indicating that benzylation had occurred. In particular, Examples 2-1 and 2-2 showed that the [P 4444 In the comparative example 2-1, in which an aqueous solution of sodium hydroxide was used, the treatment temperature in the second step was set to 25° C., and it was found that benzylation proceeded efficiently. On the other hand, in the comparative example 2-1, in which an aqueous solution of sodium hydroxide was used, it was found that almost no benzylation occurred when the treatment temperature in the second step was set to 25° C. In addition, in Example 2-3, benzylation proceeded more than in Comparative Example 2-1 in which an aqueous sodium hydroxide solution was used in the first step, but the extent was smaller than in Examples 2-1 and 2-2.
[0062] The second modified wood (SS2) obtained in Comparative Example 2-2 was sufficiently benzylated, but because an aqueous sodium hydroxide solution was used in the first step, a longer treatment time was required compared to Examples 2-1 and 2-2, even including the second step. Furthermore, when modified under the conditions in Comparative Example 2-2, the surface of the second modified wood (SS2) sometimes darkened to a color close to black compared to the defatted wood chips before treatment. A colorimeter was used to compare the color difference before and after treatment of the darkened second modified wood (hereinafter referred to as "SS2-2"), and the results were ΔL*=-16.5 and ΔE*ab=16.6 (see Table 3). On the other hand, the second modified wood (RR1) obtained in Example 2-1 had ΔL*=4.7 and ΔE*ab=6.7, and was slightly whiter than the defatted wood chips before treatment (see Table 3). Therefore, according to the present invention, since the treatment temperature does not need to be high in the first and second steps, the difference between the hue of the obtained second modified wood and the hue of the raw wood before treatment can be reduced, and depending on the type of raw wood, it becomes easy to design products using the second modified wood based on its hue.
[0063] [Table 3]
[0064] The surfaces of the second modified wood (RR1) obtained in Example 2-1 and the second modified wood (SS2-2) obtained in Comparative Example 2-2, together with the surface of the defatted wood piece before treatment, were observed with an optical microscope "VHX-970F" (model name) manufactured by Keyence Corporation. FIG. 5 is an optical microscope image of the surface of the defatted wood piece, FIG. 6 is an optical microscope image of the surface of the second modified wood (RR1), and FIG. 7 is an optical microscope image of the surface of the second modified wood (SS2-2). According to FIG. 7, it can be seen that the surface of the second modified wood (SS2-2) has countless fine scratches that were not seen in FIG. 5 (defatted wood piece before treatment). On the other hand, according to FIG. 6, the surface of the second modified wood (RR1) was almost the same as the defatted wood piece before treatment. Furthermore, the infrared absorption spectrum of the second modified wood (SS2-2) is shown in Fig. 8. According to Fig. 8, compared with the defatted wood piece in Fig. 4, the 3000 to 3600 cm -1 Although the absorption peak intensity of 3020-3080 cm originating from the benzyl moiety in the benzyloxy group has decreased, -1 , 1592~1612cm -1 , 1454~1496cm -1 , about 736cm -1 , about 696cm -1 From this result, it is considered that in the second modified wood (SS2-2) darkened under the conditions of Comparative Example 2-2, the benzylation reaction did not proceed, and only the modification of the wood components occurred due to the heat treatment.
[0065] Next, the results of the contact angle measurement of the degreased wood chips (raw wood), the second modified wood chips (RR1) of Example 2-1, and the second modified wood chips (SS2-2) of Comparative Example 2-2 that were darkened are shown in Table 4. In all cases, the contact angle value decreased with the passage of time after the dripping, but the contact angle of the second modified wood chips (RR1) was greater than that of the degreased wood chips, indicating that the surface was hydrophobized. On the other hand, the contact angle of the darkened second modified wood chips (SS2-2) was smaller than that of the degreased wood chips. In particular, the contact angle of 0° indicates that the water droplets dripped during the measurement immediately seeped into the wood chips. It was shown that the hydrophobicity of the second modified wood chips (SS2-2) was significantly reduced. From the above, it was found that unintended darkening occurred in the case of the method of performing the first step using an aqueous sodium hydroxide solution. It was also found that the second modified wood chips that underwent such changes not only lost their design properties, but also showed a large difference in physical properties.
[0066] [Table 4]
[0067] In the above examples, the first and second steps were carried out in sequence, but depending on the type of modifying compound, it is also possible to produce the second modified wood by having the raw wood, compound (A), and the modifying compound coexist in the reaction system. [Industrial Applicability]
[0068] The modified wood (second modified wood) obtained by the present invention is suitable as a raw material for manufacturing wood-based molded products that have the texture of wood and that constitute daily necessities, furniture and furnishings, building materials and construction components, housings for electrical appliances or audio equipment, vehicle components, etc.
Claims
1. A method for producing modified wood, comprising a first step of contacting raw wood with a compound (A) represented by the following general formula (1): [R + ][OH - ] (1) (In the formula, R + is an organic cation.)
2. The organic cation R + The method for producing modified wood material according to claim 1, wherein is a quaternary phosphonium cation.
3. 3. The method for producing modified wood material according to claim 1, wherein in the first step, the raw wood material is contacted with an aqueous solution of the compound (A).
4. The method for producing modified wood material according to any one of claims 1 to 3, further comprising a second step of contacting the modified wood material obtained in the first step with a modifying compound.
5. The method for producing modified wood material according to claim 4, wherein the modifying compound used in the second step is a halogenated hydrocarbon, and forms a hydrocarbon group on the surface of the modified wood material.
6. 6. The method for producing modified wood material according to claim 5, wherein the halogenated hydrocarbon is a chlorine compound or a bromine compound.
Citation Information
Patent Citations
Treatment of wood
JP1990047001A
Method for dyeing woody veneer and manufacture of woody decorative veneer
JP1999170217A
Method of modifying wood and modified wood obtained by this method
JP2010221645A
Method for manufacturing a fine cellulose fiber
JP2014234457A
Alkali cellulose, and method for producing the same or derivative thereof
JP2011037924A
Cited By
Compressor with bottom cover and bearing block arrangement
US12497966B2